Crystallization of Ge in ion-irradiated amorphous-Ge/Au thin films. Issue 4 (18th December 2019) - Maity, G.; Ojha, S.; Dubey, S.; Kulriya, P. K.; Sulania, I.; Dhar, S.; Som, T.; Kanjilal, D.; Patel, Shiv P.
Abstract : Herein, the structural, optical, and electrical properties of Au-induced crystallization in amorphous germanium (a-Ge) thin films are presented for future solar energy material applications. Abstract : Herein, the structural, optical, and electrical properties of Au-induced crystallization in amorphous germanium (a-Ge) thin films are presented for future solar energy material applications. The a-Ge/Au thin films on quartz substrate were prepared via the e-beam and thermal evaporation techniques, respectively. The as-prepared samples were irradiated with 100 MeV Ni 7+ ions at different fluences of 1 × 10 12 ions per cm 2, 5 × 10 12 ions per cm 2, 1 × 10 13 ions per cm 2 and 5 × 10 13 ions per cm 2 . The ion irradiation did not result in the crystallization of Ge; instead, an increase in ion fluence decreased the Au crystallite size, which ultimately deteriorated the Au crystallization. The ion-irradiated samples were post-annealed for 4 h at a fixed temperature of 300 °C to achieve the crystallization of Ge. The post-annealing of the ion-irradiated samples led to the crystallization of Ge, where the crystallization of Ge was better for the samples irradiated at high fluence, leading to a smaller grain size corresponding to a high grain boundary, and hence high defect sink density. The energy bandgap of crystalline Ge was determined using reflectance and transmittance spectra, which was found to be low (∼0.64 eV) at higher fluence. The field-emission scanning electron microscopy and atomic force microscopy analyses show that the surface microstructure changed for the post-annealed samples irradiated at different fluences. The role of the fractal-like surface microstructure in multiple scattering of light on the film surface is discussed. Thus, the lower values of resistivity and sheet resistance as well as good optical properties of Ge make it a promising material for future poly-Ge-based solar cell applications.